Interdepartmental Coordination for Maine’s Young Children with Disabilities - Cobo-Lewis, Alan (Maine Policy Review, 2009)
Alan B. Cobo-Lewis describes Maine’s system of services for young children with disabilities. He notes that families of young children with disabilities face challenges in navigating Maine’s service structure. There can be delays before children get appropriate evaluation, and there are sometimes problems with inter-agency referrals. Cobo-Lewis makes a number of recommendations regarding data linkage; coordination of eligibility determination from different funding streams; updating inter-agency agreements; and creation of a more efficient state departmental structure for services to children with disabilities
Keywords: Maine; children with disabilities; disability services